FORECASTING THE AEROIN COMPOSITION OF AIR IN THE PRESENCE OF NATURAL AND ARTIFICIAL SOURCES OF IONIZATION: Array - Frolov, V.; Panova, O.; Zozulya, S. (Municipal economy of cities. Series: «Economy science», 2022)
It is shown that for the design of buildings and individual rooms with normative concentrations of light air ions of both polarities, a preliminary estimated assessment of the dynamics of this indicator in space and time is appropriate. In the general case, it is possible to use the continuity equation for weakly ionized plasma for one direction. This is due to the low concentration of air ions in the air. The ratio of molecular kinetic theory of gases is used to determine the necessary indicators - the average lifetime of air ions, free path length. To determine the average speed - Maxwell’s distribution. It is shown that the propagation of air ions due to diffusion processes is insignificant, and the corresponding calculations have large errors. Calculations on the propagation of air ions by directed air movement from the source of artificial ionization are given. The distribution of air ion concentrations can be most accurately calculated taking into account their recombination, deposition on heavy air ions and neutral suspended parts (fine dust and aerosols). Relevant coefficients are mostly issued from reference sources. If there are electrostatic fields in the premises, generated due to the triboelectric effect and other factors, it is necessary to take into account the deposition of air ions on these surfaces. In order to correctly determine the concentrations of air ions, in addition to the values of the mobility of negative and positive air ions, data on electrostatic field strengths are required. The values of such fields are unpredictable, so they are measured by appropriate instruments in similar conditions. Verification of calculated data using electrostatic charge meters and air ion counter proved the reasonable convergence of expected and actual data. It is advisable to develop two- and three-dimensional models of the propagation of air ions of both polarities in rooms of different purposes, configurations of equipment placement, the presence of artificial ionization sources and directional air movement.